2021
DOI: 10.1097/mlr.0000000000001656
|View full text |Cite
|
Sign up to set email alerts
|

Suicide Among American Indian and Alaska Native Veterans Who Use Veterans Health Administration Care

Abstract: Background: American Indian and Alaska Natives (AI/ANs) veterans may be at elevated risk for suicide, but little is known about suicide among this population. Methods:We conducted a retrospective cohort analysis of AI/AN veterans who received health care services provided or paid for by the Veterans Health Administration (VHA) between October 1, 2002, and September 30, 2014, and who were alive as of September 30, 2003. Age-specific and age-adjusted suicide rates through 2018, per 100,000 person-years (PY) at r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 18 publications
(49 reference statements)
1
8
0
Order By: Relevance
“…Given that American Indian/Alaska Native (AI/AN) individuals have higher rates of suicide than other racial/ethnic groups (Leavitt et al, 2018) and the trend of increasing rates of suicide among AI/AN veterans who use VA health care (Mohatt, Hoffmire, et al, 2022), Mohatt, Begay, et al (2023) conducted a scoping review of programs to identify strong practices for preventing suicide among AI/AN veterans. With the goal of creating suicide prevention programs to meet the needs of AI/AN veterans, the authors followed scoping review guidelines established by Arksey and O’Malley (2005).…”
Section: Literature Reviewsmentioning
confidence: 99%
“…Given that American Indian/Alaska Native (AI/AN) individuals have higher rates of suicide than other racial/ethnic groups (Leavitt et al, 2018) and the trend of increasing rates of suicide among AI/AN veterans who use VA health care (Mohatt, Hoffmire, et al, 2022), Mohatt, Begay, et al (2023) conducted a scoping review of programs to identify strong practices for preventing suicide among AI/AN veterans. With the goal of creating suicide prevention programs to meet the needs of AI/AN veterans, the authors followed scoping review guidelines established by Arksey and O’Malley (2005).…”
Section: Literature Reviewsmentioning
confidence: 99%
“…Recently, increased efforts have focused on identifying trends in suicide rates by subgroups, including by race and ethnicity [8,9], to help guide tailored prevention efforts. Against the backdrop of findings which suggested a decrease in the overall general United States population 2019 suicide rate, Ramchand et al conducted a cross-sectional study to examine trends in suicide rates among United States racial and ethnic groups [8].…”
Section: Introductionmentioning
confidence: 99%
“…A recent analysis undertaken to explore trends among AI/AN veterans provides further support for these assertions. Mohatt et al conducted a retrospective cohort analysis of AI/AN individuals who received care within the Veterans Health Administration between 2002 and 2014 and found that the age-adjusted suicide rates more than doubled over the 15-year observation period (19.1-47.0/100,000 Person Years) [9]. Also of note, was the finding that the youngest age group (18-39) exhibited the highest risk [9].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Department of Veterans Affairs, 2020). Among AI/AN veterans who use U.S. Veterans Health Administration care suicide rates increased 146% from 2004 to 2018 (19.1–47.0 per 100,000; Mohatt et al, in press).…”
mentioning
confidence: 99%